The significance of Holter electrocardiography in the etiological evaluation of transient ischemic stroke - Yıldız Arslan; Burcu Selbest Demirtaş; Cenk Ekmekci; Figen Tokuçoğlu; Yaşar Zorlu (Brain Circulation, 2020)
BACKGROUND: Transient ischemic attack (TIA) is a common neurovascular disorder associated with a higher risk of stroke within the first 24 h after the first event. Acute cerebral and arterial neuroimaging combined with long-term electrocardiography (ECG) monitoring have been proven to be useful in determining etiology. Cardio-embolism constitutes 20%–26% etiology of TIAs most of them with atrial fibrillation (AF). Investigation of AF after TIA is very important because oral anticoagulants can reduce the risk of subsequent stroke by two thirds. MATERIALS AND METHODS: The present study included 45 patients suffering from TIA with undetermined source according to the Trial of Org 10172 in Acute Stroke Treatment criteria; the control group (n = 45) was selected from the patients admitted to cardiology outpatient clinic with nonspecific complaints without cerebrovascular and/or cardiovascular disease. All patients underwent echocardiography and 24 h Holter ECG monitoring (HM). RESULTS: There was no significant difference between the patient group and the control group in terms of age and gender. Cholesterol, low-density lipoprotein and urea levels, left atrium diameters and the incidence of hypertension, coronary artery diseases, and AF were significantly higher in TIA group (P < 0.05). In the results of HM, there were six patients with AF in the study group, and in the control group, there was no patients with AF (P = 0.03). DISCUSSION AND CONCLUSION: In acute phase of TIA, 24 h HM is important for determining the etiology and selecting an appropriate treatment that can protect patients from subsequent strokes.